Perubahan Penutupan Lahan Di Taman Nasional Way Kambas - Danang Arif Maullana; Arief Darmawan (Jurnal Sylva Lestari, 2014)
Land cover changes in Way Kambas National Park (TNWK) changes rapidly. Data on changes in land cover in 1996, 2002 and 2010 in TNWKanalyzed by using remote sensing and Geographic Information Systems (GIS). Analysis also includes changes in land cover in each zoning park management. The research was conducted in June-September 2012 at the Way Kambas National Park. Data collected in the form of Landsat ETM + and TM (1996, 2002, and 2010), field verification points, and attribute data in the form of zoning. Spatial data processed with ERDAS imagine software version 8.5 and Arc View version 3.3, while the data is processed by descriptive attributes and analyzed qualitatively. Land cover types in the Way Kambas National Park is divided into 9 classes of forest, wetland forests, wetlands, shrubs, reeds, open land, water bodies, lading, and no data (cloud and cloud shadow). The largest land cover on the forest zone and the intensive use of coarse grass while special conservation zone and the core zone has the largest forest cover in the form of forest. Keywords: GIS, land cover, Way Kambas National Park